Efficient total synthesis of decarestrictine D - Guptali, Priti; Kumar, Pradeep (European Journal of Organic Chemistry, 2008)
An efficient total synthesis of decarestrictine D has been achieved using cross-metathesis or ring-closing metathesis and Yamaguchi macrolactonization as key steps. The stereogenic centres were generated by means of hydrolytic kinetic resolution (HKR) and Sharpless asymmetric dihydroxylation (AD).
Keywords: Cross metathesis; Hydrolytic kinetic resolution; Macrolides; Ring-closing metathesis; sharpless asymmetric dihydroxylation

Carbohydrate-based synthesis of the C13-C22 fragment of amphidinolide X - Gurjar, Mukund K.; Yellol, Gorakh S.; Mohapatra, Debendra K. (European Journal of Organic Chemistry, 2012)
A facile carbohydrate-based route was developed for the synthesis of the tetrahydrofuran (C13C22) fragment of amphidinolide X. Starting from L-sorbose, the key reactions followed include the stereoselective synthesis of a quaternary center at C1, BartonMcCombie deoxygenation at C2, Mitsunobu inversion at C3, and chain elongation by a Wittig reaction at C5.
Keywords: Cytotoxicity; Macrolides; Mitsunobu inversion; Natural products; Wittig reactions